Impact of Cripple Part Storage Management System Improvement on the Overall Equipment Effectiveness in an Automotive Spare Part Manufacturing Company - Erwin Sitompul; Muhammad Junedi; Antonius Suhartomo (President University, 2023)
Improving productivity and performance is a continuous process in all manufacturing companies. Since a product fabrication process mostly consists of many production and work steps, there is always an opportunity for small improvement. If conducted consistently and continually, a series of small improvements can yield a considerable increase in overall productivity and performance. In this paper, the effort undertaken in an automotive spare part manufacturing company to reduce downtime due to the dandori process is presented. Dandori is the installation or setup required between the production of two different spare part types. The setup includes stocking in incomplete lots of product, or the cripple parts, of one type and stocking out the cripple parts of the other. The existing dandori process consisted of 12 steps and required 190.2 seconds. The development of a storage management system was proposed to reduce the downtime required to fill the production check sheets and to find the correct drawer in the storage room. The new dandori process consists of 19 steps and requires 140.4 seconds. The manual check sheet filling was replaced with QR code scanning and data input on a computer, while the manual finding of the correct drawer was assisted by the LED indicators. Production data for the duration 4 months before and 4 months after the improvement was analyzed. The availability rate of the process increases from 84.87% to 89.34%, and the overall equipment effectiveness (OEE) increases from 73.11% to 78.37%. The obvious increases encourage further continuous improvement cycle in the company.